Distraction effects of contextual advertising on online news processing: an eye-tracking study. Issue 8 (2nd August 2016) - Wojdynski, Bartosz W.; Bang, Hyejin
ABSTRACT: Although recent scholarship has shown that congruency between editorial content and display advertising on web pages can lead to favourable outcomes for the advertiser, it is unclear whether these gains for advertisers come at the expense of users' ability to process the content. To examine whether contextual in-page advertising distracts users during information processing, a 2 (target message argument type: weak/strong) × 2 (ad relevance: high/low) between-subjects factorial experiment ( N = 99) examined how readers of a news article about risks associated with texting while driving (a) paid attention to the article, (b) paid attention to the advertisements, and (c) were persuaded by the article contents. Participants' visual attention was captured unobtrusively using a device-mounted eye-tracking device. The findings show that readers were more likely to be persuaded by weaker arguments when the article was presented alongside highly relevant display ads than when the article was presented alongside less relevant ads. Readers also paid greater attention to relevant ads than irrelevant ads, and, surprisingly, readers in the strong argument condition paid more attention to the story content when it was presented alongside relevant ads. The implications for theories of visual attention and for online content publishers are discussed.